Determining the impact of welding parameters on the arc stability of drawn arc submerged welding for reinforcing rods A500C - Yaros, Yuriy; Hladchenko, Dmytro; Drahan, Stanislav (Eastern-European Journal of Enterprise Technologies, 2026)
Stability of the electric arc process during welding has been investigated in this study. A weld seam is produced in 2–4 seconds only, so the quality of connection directly depends on the stability of welding arc burning. The features of the electric arc process are determined by a combination of welding mode parameters: current, welding duration, lifting height, and preliminary rod departure. Establishing the mode parameters that enable stable arc burning is a complex practical task, solving which by the selection method does not warrant the optimal result. This paper reports results of investigating the welding of A500C reinforcing bars with a drawn arc in flux. The values of the coefficients of variation in the current and voltage, obtained by statistical processing of the welding arc oscillograms, were chosen as a criterion for quantitative assessment of the stability of the electric arc process. It was established that in the entire range of the studied modes , that is, the electric arc process is stable. The plots of variation coefficients depending on the welding current have extrema that correspond to the most stable welding mode. It is this feature of the variation coefficient function that makes it possible to determine the optimal value for the welding current. The influence of the welding mode parameters on the weld formation process was investigated. The resulting regression dependences enable predicting the volume of molten metal and, as a result, the geometric dimensions of the weld. Based on the study's results, an engineering methodology for searching for optimal welding mode parameters was devised. The welding mode parameters for reinforcing bars with a diameter of 16 mm were calculated. The established modes were tested when welding a batch of control samples in the amount of 10 pieces; the result is that the geometric dimensions and shape of the welds meet the requirements from DSTU B V.2.6-169:2011